Design of modern steel railway bridges - Unsworth, John F. (CRC Press, Taylor & Francis, 2010)
Perhaps the first book on this topic in more than 50 years, Design of Modern Steel Railway Bridges focuses not only on new steel superstructures but also outlines principles and methods that are useful for the maintenance and rehabilitation of existing steel railway bridges. It complements the recommended practices of the American Railway Engineering and Maintenance-of-way Association (AREMA), in particular Chapter 15-Steel Structures in AREMA's Manual for Railway Engineering (MRE). The book has been carefully designed to remain valid through many editions.